Empirical Analysis of the Impact of Debt Servicing on the Performance of the Nigerian Economy - Okosu, Napoleon David (Advances in Social Sciences Research Journal, 2024)
The study interrogates the impact of debt servicing on the performance of the Nigerian economy. Using yearly time series data from 1980 to 2022 obtained from Debt Management Office, Central Bank of Nigeria and the World Bank National Account. The dependent variable in the model was Growth Rate of Gross Domestic Product (GRGDP), and the explanatory variables were External Debt Service (EDS), Domestic Debt Service (DDS), Interest Rate (INR) and Exchange Rate (EXR). The methodology utilized was the popular Auto-Regressive Distributed Lag (ARDL) model. Findings reveal that in the long run, EDS has a positive though insignificant nexus to GRGDP. For DDS the relationship is a significant negative association with GRGDP. Whilst for Exchange Rate a positive and significant relationship was found. INR had a positive but insignificant nexus to GRGDP. Based on the findings the study recommended the review of Nigeria’s debt sustainability plan, imposition of strict limits on amount to borrow, type and the sources from where to borrow. Also, Nigeria government should ensure that debt or borrowings are channeled towards project that are self-liquidating and infrastructure development as well as minimize the use of huge debt to finance recurrent expenditures.